Modeling geomorphological processes in the coastal area using soft computing approach: a case study from the Island of Corfu (Greece). - Gournellos, Th.; Poulos, S.; Vassilopoulos, A.; Evelpidou, N. (International Conference on ‘Quaternary coastal morphology and sea level changes’, 2003)
Coastal areas are the result of a complex interaction of many factors such as rock properties, geomorphological processes and wave action. We approach these dynamic landscapes using fuzzy set theory. As input variables we use rock’s erodibility, slope gradient, (drainage density,) vegetation and land use and wave characteristics. Next we formulate fuzzy logical rules to transform input variables to output ones. The output of the system represents the coastal depositional and erosional processes. As a case study we choose the island of Corfu (Greece) which presents lithologies very vulnerable to erosion and receives very high amount of rainfalls, in relation to the rest of the Greek territory. All this procedure has been developed using a loose coupling system of a flexible GIS platform and the proper environment to process fuzzy variables.